2017
DOI: 10.1210/en.2017-00470
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Action via the Androgen Receptor in Neurons Within the Brain Positively Regulates Muscle Mass in Male Mice

Abstract: Although it is well established that exogenous androgens have anabolic effects on skeletal muscle mass in humans and mice, data from muscle-specific androgen receptor (AR) knockout (ARKO) mice indicate that myocytic expression of the AR is dispensable for hind-limb muscle mass accrual in males. To identify possible indirect actions of androgens via the AR in neurons to regulate muscle, we generated neuron-ARKO mice in which the dominant DNA binding-dependent actions of the AR are deleted in neurons of the cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Hence, the observed effects in this NeurARKO model are due to the selective loss of AR function specifically in the brain and pituitary. Furthermore, in support of our findings, using quantitative real-time PCR analysis in the same mouse model, Davey et al[41] observed a > 99% reduction in AR exon 3 mRNA in the cortex, hypothalamus, forebrain, and olfactory bulb, a 77% decrease in the cerebellum, and a 35% reduction in the pituitary.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, the observed effects in this NeurARKO model are due to the selective loss of AR function specifically in the brain and pituitary. Furthermore, in support of our findings, using quantitative real-time PCR analysis in the same mouse model, Davey et al[41] observed a > 99% reduction in AR exon 3 mRNA in the cortex, hypothalamus, forebrain, and olfactory bulb, a 77% decrease in the cerebellum, and a 35% reduction in the pituitary.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our NeurARKO (which exhibits a 35% reduction of pituitary AR expression) did not present with reduced LH in the afternoon of proestrus. This inconsistency may be explained by the presence of more functional AR mRNA in the pituitary in our model [41], possibly due to an earlier time of collection prior to the onset of the LH surge or potential hypothyroidism in the PitARKO model due to this model being created by the use of gonadotropin alpha subunit (αGSU)-Cre that is expressed in not only pituitary gonadotropes but also the thyrotropes. E2-treated NeurARKO females lack an LH surge, and while these mice appeared to cycle at a normal frequency, the cycles appear more irregular than those of WT females.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, wheel running activity, which we have previously established as a sensitive marker of androgen activity, remained unaltered after AR inactivation in neurons. However, seminal vesicle weight, a frequently used readout for androgen levels, was increased in N‐ARKO mice, despite less than in previous N‐ARKO mouse models with a complete neuronal AR inactivation in the hypothalamus . Because seminal vesicle weight might be more sensitive than serum T reflecting changes in androgen activity in male rodents, we determined the bone phenotype of N‐ARKO mice after ORX and hormone replacement in order to rule out potential confounding from subtle alterations in sex steroid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Here, inactivation of AR in neurons did not recapitulate the detrimental effects of androgen deficiency on hindlimb muscle mass, grip strength, and wheel running activity, thus excluding the possibility that the bone phenotype of N‐ARKO mice was secondary to a loss of muscle function. Our results differ from those obtained by Davey and colleagues showing that AR signaling in brain, including hypothalamic regions, positively regulates hindlimb muscle mass. Whether differences between studies reflect a role for hypothalamic AR remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation